Barbie. 2, Big dreams, best friends - Kuhn, Sarah (Author) (Barbie., 2017)
When her designs for a rock and roll tour are destroyed opening night, Barbie is challenged to find who ruined her designs while navigating the world of rock music, fashion, and celebrity.